Telomere Length Declines in Persons With Human Immunodeficiency Virus Before Antiretroviral Therapy Start but Not After Viral Suppression: A Longitudinal Study Over >17 Years. (16th December 2021) - Schoepf, Isabella C; Thorball, Christian W; Ledergerber, Bruno; Kootstra, Neeltje A; Reiss, Peter; Raffenberg, Marieke; Engel, Tanja; Braun, Dominique L; Hasse, Barbara; Thurnheer, Christine; Marzolini, Catia; Seneghini, Marco; et al.
Abstract: Background: In people with human immunodeficiency virus (PWH), long-term telomere length (TL) change without/with suppressive antiretroviral therapy (ART) and the contribution of genetic background to TL are incompletely understood. Methods: We measured TL change in peripheral blood mononuclear cells by quantitative polymerase chain reaction in 107 Swiss HIV Cohort Study participants with longitudinal samples available both before and during suppressive ART. We applied mixed-effects multilevel regression to obtain uni-/multivariable estimates for longitudinal TL dynamics including age, sex, and CD4/CD8 ratio. We assessed the effect of (1) individual antiretrovirals and (2) an individual TL-polygenic risk score ([TL-PRS] based on 239 single-nucleotide polymorphisms) on TL in 798 additional participants from our previous longitudinal studies. Results: During untreated human immunodeficiency virus (HIV) infection (median observation, 7.7; interquartile range [IQR], 4.7–11] years), TL declined significantly (median −2.12%/year; IQR, −3.48% to −0.76%/year; P  = .002). During suppressive ART (median observation, 9.8; IQR, 7.1–11.1 years), there was no evidence of TL decline or increase (median + 0.54%/year; IQR, −0.55% to + 1.63%/year; P  = .329). The TL-PRS contributed to TL change (global P  = .019) but particular antiretrovirals did not (all P  > .15). Conclusions: In PWH, TL is associated with an individual PRS. Telomere length declined significantly during untreated chronic HIV infection, but no TL change occurred during suppressive ART. Abstract : A total of 107 Swiss HIV Cohort Study participants contributed longitudinal samples. During untreated chronic HIV infection (median observation time, 7.7 years) but not during suppressive antiretroviral therapy (median observation time, 9.8 years), we recorded significant telomere length decline.